Optimization and comparison of headspace hot injection and trapping, headspace solid-phase microextraction, and static headspace sampling techniques with gas chromatography–mass spectrometry for the analysis of volatile compounds in kimchi. (December 2020) - Hwang, Ye-Seul; Yang, Ji-Su; Lee, Hae-Won; Ha, Ji-Hyoung
Abstract: The identification of volatile compounds (VCs) related to flavors is important for confirming food quality, and instrumental techniques are required to effectively and accurately identify and determine the VCs responsible for such flavors. The VCs related to kimchi flavor were analyzed by headspace hot injection and trapping (HS-HIT), which is a type of multiple headspace sample enrichment sampling technique. For the HS-HIT sampling technique, the cool injection system temperature was optimized to −40 °C and the multiple sampling frequency was optimized to nine injections. Moreover, HS-HIT was compared with static headspace (SHS) and headspace solid-phase microextraction (HS-SPME) sampling techniques for the VC analysis of kimchi. The overall peak intensities in the total ion chromatograms (TICs) with SHS and HS-SPME were lower than with HS-HIT. Although the HS-HIT sampling technique was complementary to the HS-SPME sampling technique for VC analysis, it allowed more sulfur compounds characteristic of kimchi to be identified than the SHS and HS-SPME sampling techniques. Therefore, we recommend the use of the HS-HIT sampling technique with GC-MS for identifying the VCs associated with kimchi flavor. This study confirmed the usefulness of the HS-HIT sampling technique for the analysis of VCs. Graphical abstract: Image 1 Highlights: Volatile compounds in kimchi were evaluated and compared by different techniques. Hot injection and trapping (HIT) sampling with GC-MS yielded the best results. HIT sampling detected almost all compounds such as characteristic sulfur compounds. HIT was simpler, showing higher sensitivity than those of conventional techniques. Sampling was useful for flavor analyses of fermented foods, specifically kimchi.